2018
DOI: 10.1175/jcli-d-17-0212.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spatial and Temporal Performances of ERA-Interim Precipitation and Temperature in Mainland China

Abstract: ERA-Interim has been widely considered as a valid proxy for observations at global and regional scales. However, the verifications of ERA-Interim precipitation and temperature in mainland China have been rarely conducted, especially in the spatial and long-term performances. Therefore, in this study, we employed the interpolated ground station (STA) data to evaluate the spatial and temporal patterns and trends of ERA-Interim precipitation and temperature during 1980–2012. The results showed that relatively wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 71 publications
4
63
0
Order By: Relevance
“…The unit of soil moisture is m 3 /m 3 . The monthly SAT and precipitation of ERA‐Interim from 1979 to 2017 are also used in this study, which is in good agreement with observed data over East Asia (Lin et al, ; Liu et al, ; Liu et al, ).…”
Section: Methodssupporting
confidence: 81%
“…The unit of soil moisture is m 3 /m 3 . The monthly SAT and precipitation of ERA‐Interim from 1979 to 2017 are also used in this study, which is in good agreement with observed data over East Asia (Lin et al, ; Liu et al, ; Liu et al, ).…”
Section: Methodssupporting
confidence: 81%
“…Compared to the ERA-Interim, ERA5 show a little improvement in reproducing wind over land [34,35], and ERA-Interim show best performance in wind speed [36]. In addition, ERA-Interim have a good ability in reproducing the temperature and precipitation over mainland China [38], but its performance in reproducing the near-surface wind is not clear.…”
Section: Introductionmentioning
confidence: 94%
“…For example, Gao et al [22] and Wang et al [24] have verified that the reanalysis data could be an alternative to observations in areas lacking data because of their resolution and long-time series. Liu et al [25] concluded that the researchers should be careful when using ERA-Interim precipitation and temperature data in complex topography areas. Gao et al [22] concluded that ERA-Interim is generally reliable for climate change studies over the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%